Protection for Sale under Monopolistic Competition: An Empirical Investigation - CHANG, Pao Li (Institutional Knowledge at Singapore Management University, 2006)
This paper proposes a general empirical framework to estimate the protection-for-sale model, where the protection regime shifts according to a sector's market structure (perfectly or monopolistically competitive). We base the protection structure on Grossman and Helpman (1994) for the subset of perfectly competitive sectors and on Chang (2005) for the subset of monopolistically competitive sectors. The two protection regimes are simultaneously estimated with joint constraints. The results of the J-test consistently reject the homogeneous (perfect competition) protection-for-sale model often adopted in previous literature and suggest a direction of improvement toward the proposed heterogeneous protection structure model.